Analisis Perencanaan dan Pengendalian Obat Kategori A dengan Metode ABC-VEN dan EOQ di IFRS RSIS Mojokerto - Mustika Wati; Ismi Rahmawati; Ika Purwidyaningrum (Jurnal Farmasi Indonesia, 2022)
The high residualvalue of drug inventory at IFRS RSIS Mojokerto indicates that drug management has not been managed optimally. The priority scale of supervision and control at planning stage needs to be carried out using the ABC-VEN method analyzing and calculating the EOQ value in order to achieve the most economical ordering value to avoid overstock. The purpose of this study was to determine drug classificationusing the ABC-VEN method, planning control using with EQQ and measuringthe efficiency value at IFRS RSIS Mojokerto. The design of this research is descriptive quantitative. Retrieval of retrospective data from the January-October 2020 financial statement at IFRS RSIS Mojokerto. The data were analyzed by ABC-VEN to get categoryA drugs. Drug inventory control was calculated by calculating the value of EOQ,ROP, efficiency value by calculating ITOR. The results of drug classification using the ABC-VEN method obtained categoryA drugs absorbing 68.05% of the total investment value. Control of planning category A drug needs resulted in the value of the remaining inventory dropping from 48.4% to 36% of the total inventory value, ITOR increased from 2.0 to 4.1 times per month. The conclusion of the ABC-VEN, EOQ and ROP analysis can be used to determine the priority scale of procurement and control to avoid over-stocking of drug supplies in the hospital.